Colorectal cancer incidence following a negative colonoscopy in fecal immunochemical test-based screening: a nationwide cohort study after 8 years of screening in Denmark - Larsen, Pernille T.; Jørgensen, Susanne F.; Rasmussen, Morten; Andersen, Berit; Cross, Amanda J.; Njor, Sisse H. (Endoscopy, 2025)
Screening participants with a positive fecal immunochemical test (FIT) result and a subsequent negative colonoscopy are quarantined from the Danish bowel cancer screening program for 8 years. This recommendation is based on evidence from settings other than FIT-based screening, but referral of this evidence is not necessarily sufficient. We estimated the colorectal cancer (CRC) risk among these FIT-positive/colonoscopy-negative individuals and compared it with the risk in a historical unscreened population.Using national health registers in Denmark, we compared 29 936 participants with a positive FIT but negative colonoscopy with 720 850 randomly selected unscreened controls born 9 years earlier (ratio 1:24). Controls were assigned a pseudo-colonoscopy date 9 years prior to the negative colonoscopy group. We examined cases per 10 000 person-years and estimated relative risks (RR) and 95%CIs for CRC.After 8 years’ follow-up, CRC risk was lower among FIT-positive/colonoscopy-negative participants compared with controls (RR 0.72, 95%CI 0.61–0.84). By age group and sex, the lower risk was only evident for women and men in their 60s (RR 0.67 [95%CI 0.47–0.96] and RR 0.65 [95%CI 0.48–0.88], respectively) and men in their 70s (RR 0.60 [95%CI 0.44–0.84]).The overall risk for CRC was lower for individuals with a positive FIT but negative colonoscopy compared with unscreened controls. However, the lower risk might not justify 8 years of quarantine, especially for women and younger age groups. Individualized screening is warranted and transfer of evidence from non-FIT screening should be done carefully.